2013
DOI: 10.1063/1.4818266
|View full text |Cite
|
Sign up to set email alerts
|

Memory effect and triplet pairing generation in the superconducting exchange biased Co/CoOx/Cu41Ni59/Nb/Cu41Ni59 layered heterostructure

Abstract: We fabricated a nanolayered hybrid superconductor-ferromagnet spin-valve structure, the resistive state of which depends on the preceding magnetic field polarity. The effect is based on a strong exchange bias (about -2 kOe) on a diluted ferromagnetic copper-nickel alloy and generation of a long range odd in frequency triplet pairing component. The difference of high and low resistance states at zero magnetic field is 90% of the normal state resistance for a transport current of 250 μA and still around 42% for … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 51 publications
0
19
0
1
Order By: Relevance
“…For example, they can operate as autonomous and persistent phase batteries -one of key elements of quantum [1,[5][6][7][8][9][10][11][12][13][14] and digital Josephson electronics [2,3,15,16]. Such junctions can be also used for development of novel types of cryogenic memory [17][18][19][20][21][22]. The π-phase shift is most commonly needed, e.g., for bringing the flux-qubit to the degeneracy point [1,[5][6][7], for realization of complementary digital Josephson electronics [2,3,15,16] and for maximum distinction between 0 and 1 state in a memory cell [17].…”
Section: Introductionmentioning
confidence: 99%
“…For example, they can operate as autonomous and persistent phase batteries -one of key elements of quantum [1,[5][6][7][8][9][10][11][12][13][14] and digital Josephson electronics [2,3,15,16]. Such junctions can be also used for development of novel types of cryogenic memory [17][18][19][20][21][22]. The π-phase shift is most commonly needed, e.g., for bringing the flux-qubit to the degeneracy point [1,[5][6][7], for realization of complementary digital Josephson electronics [2,3,15,16] and for maximum distinction between 0 and 1 state in a memory cell [17].…”
Section: Introductionmentioning
confidence: 99%
“…After that, when the sample is saturated in negative fields the alignment is P again [6,9]. In order to estimate some magnetic parameters from the curves, the derivatives of the descending and ascending branches of the loop were calculated [18][19][20] investigated NiFe/IrMn/Co trilayers grown on Ta or Cu seed layers and found that crystalline texture influences the trilayers' magnetic properties [22]. This way, as discussed above, the difference of the H C and H EB values for S Nb when compared to those for S Ta , obtained at 6 K, may be attributed to the degree of (200) preferred orientation of the IrMn layer in S Nb .…”
Section: Resultsmentioning
confidence: 99%
“…Here g  are the integration constants. In the F layer we can assume small superconducting correlations 1 F q  to linearise the denominator of the left-hand side of (15), which leads us to the equation…”
Section: Critical Current Densitymentioning
confidence: 99%
“…Moreover, a new generation of supercomputers has been developed based on superconducting spintronics [5,6]. One of the main goals of the recent superconducting spintronics development is the creation of rapid single flux quantum logic (RSFQ) elements, such as Josephson phase batteries [7][8][9][10][11][12] and magnetic memory [13][14][15][16][17][18][19][20][21][22][23]. Both, Josephson phase batteries and magnetic memory are based on ferromagnetic Josephson junctions (FJJs).…”
Section: Introductionmentioning
confidence: 99%